Does Hormone Replacement Therapy Increase Women's Risk of Dementia?. (25th October 2022) - Shang, Yanan
Abstract : Women have a higher risk of developing dementia, particularly Alzheimer dementia (AD). The reason for a sex difference in the risk of AD is not clearly understood. Some researchers suspect that hormone changes that come with menopause may be associated with a higher risk of dementia. If so, it would be expected that replacing hormones in menopause might reduce dementia risk for women. However, the relationship between hormone replacement therapy (HRT) and dementia risk is much more complex.